Conflicts of Laws and Jurisdictions in Indonesia-related Arbitrations Seated in Singapore – Perspectives From The Tribunal - Bell, Gary F. (UI Scholars Hub, 2022)
This article discusses the issues of conflicts of laws that may arise when the parties, including an Indonesian party, have a contract governed by Indonesian law which includes an arbitration clause that states that the seat of the arbitration is Singapore. After discussing the rules of conflict of laws applicable to the choice of a substantive law governing the contract and the arbitration clause, the article discusses the difficulties that parties and the tribunal often face in an arbitration in which Indonesian law is the governing law. It then discusses conflict rules affecting the validity of the arbitration agreement and the jurisdiction of the tribunal. It finally discusses two other potentially conflictual situations that may arise.